White laminated polyester film
By applying a crosslinked coating of polycarbonate structure urethane resin and branched structure on the polyester film substrate, the blockage problem caused by condensation water is solved, while maintaining the adhesion to UV ink and the processing characteristics of the film, improving economic benefits.
Patent Information
- Application Number
- JP2024194566
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-08-02
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2040-07-10
AI Technical Summary
The prior art is difficult to avoid blockage problems caused by condensation water, especially when temperature changes, while maintaining good UV ink adhesion.
A coating of a urethane resin containing a polycarbonate structure and a branched structure is applied to the polyester film substrate, a occlusion resistance coating is formed by crosslinking, and a specific proportion of polycarbonate polyol and polyisocyanate components are synthesized, and inorganic particles are added to improve slippage and light scattering effect.
It achieves no blockage when condensate adhesion, and maintains excellent adhesion to UV ink, improving the processing characteristics and economic benefits of the film.
Smart Images

Figure 2025016739000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a white laminated polyester film, more particularly to a white laminated polyester film which exhibits reduced blocking when water is applied thereto and excellent ink adhesion, and is suitable for use as an information recording material or a printing material. [Background technology]
[0002] Biaxially oriented polyester films have excellent properties such as mechanical properties, electrical properties, and dimensional stability, and are therefore used as base films in many fields such as magnetic recording materials, packaging materials, electrical insulating materials, photosensitive materials, drawing materials, photographic materials, etc. However, when other materials are coated and laminated on the polyester film in these applications, the polyester film has the disadvantage of having poor adhesion depending on the material used.
[0003] As a method for imparting adhesiveness to the surface of a polyester film, a method is known in which various resins are applied to the surface of the polyester film to provide a coating layer having adhesive properties.
[0004] In the case of various conventional ink-adhesive polyester-based coated films, a coating layer made of a specific resin is often provided on the surface of a base polyester film (see, for example, Patent Document 1). Examples of the resin constituting the coating layer include polyester-based resins, polyurethane-based resins, acrylic-based resins, etc., either alone or in mixtures of two or more kinds, and mixtures of the above resins with specific crosslinking agents (melamine, isocyanate, etc.).
[0005] However, in such conventional technology, when transporting a film roll between indoors and outdoors in a factory, etc., especially during winter, condensation water adheres to the film roll due to the difference in temperature between the indoor and outdoor air, causing blocking problems in which the film surface and its coating layer stick to each other. This is a different type of blocking that occurs under pressure after being left in air containing normal water vapor, and it occurs only through liquid water. In other words, it was difficult to achieve both adhesion to ink adhesion and blocking resistance. In particular, it was extremely difficult to achieve both adhesion to ultraviolet-curable ink (UV ink) and blocking resistance. Seasoning is an effective way to avoid this, but it cannot be completely avoided, and the addition of a seasoning process slows down processing, leading to a decrease in productivity. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2000-229355 A Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention has been made in view of the problems of the conventional technology. That is, an object of the present invention is to provide a white laminated polyester film that has resistance to blocking when water is attached and has excellent adhesion to UV ink. [Means for solving the problem]
[0008] Means for Solving the Problems The present inventors, in the course of investigating the causes of the above problems in order to solve the above problems, discovered that the problems of the present invention can be solved when a polyester film substrate has a coating layer on at least one side thereof, and the coating layer is formed by curing a composition containing a crosslinking agent, a polyester resin, and a urethane resin having a polycarbonate structure and a branched structure, and thus completed the present invention.
[0009] That is, the present invention comprises the following: 1. A white laminated polyester film having a coating layer on at least one side of a polyester film substrate, the coating layer being formed by curing a composition containing a urethane resin having a polycarbonate structure and a branched structure, a crosslinking agent, and a polyester resin. 2. The white laminated polyester film as described in the above item 1, wherein the crosslinking agent is a compound having a tri- or higher functional blocked isocyanate group. 3. The white laminated polyester film according to the above 1 or 2, wherein the urethane resin having a polycarbonate structure and a branched structure is obtained by synthesizing and polymerizing a polycarbonate polyol component and a polyisocyanate component, and the mass ratio of the polycarbonate polyol component to the polyisocyanate component (mass of the polycarbonate polyol component / mass of the polyisocyanate component) during the synthesis and polymerization is 0.5 to 3. Effect of the Invention
[0010] The white laminated polyester film of the present invention does not cause blocking even when condensed water adheres to it, and has excellent adhesion to UV ink, particularly during low-dose processing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] (Polyester film base) In the present invention, the polyester resin constituting the polyester film substrate is polyethylene terephthalate, polybutylene terephthalate, polyethylene-2,6-naphthalate, polytrimethylene terephthalate, etc., as well as copolymerized polyester resins in which a portion of the diol component or dicarboxylic acid component of the above-mentioned polyester resins is replaced with a copolymerization component such as the following. For example, the copolymerization component may include diol components such as diethylene glycol, neopentyl glycol, 1,4-cyclohexanedimethanol, and polyalkylene glycol, and dicarboxylic acid components such as adipic acid, sebacic acid, phthalic acid, isophthalic acid, 5-sodium isophthalic acid, and 2,6-naphthalenedicarboxylic acid.
[0012] In the present invention, the polyester resin preferably used for the polyester film substrate is mainly selected from polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, and polyethylene-2,6-naphthalate. Among these polyester resins, polyethylene terephthalate is most preferable in terms of the balance between physical properties and cost. In addition, the polyester film substrate made of these polyester resins is preferably a biaxially oriented polyester film, which can improve chemical resistance, heat resistance, mechanical strength, etc.
[0013] The catalyst for polycondensation used in the production of polyester resin is not particularly limited, but antimony trioxide is suitable because it is inexpensive and has excellent catalytic activity. It is also preferable to use a germanium compound or a titanium compound. More preferable polycondensation catalysts include a catalyst containing aluminum and / or a compound thereof and a phenolic compound, a catalyst containing aluminum and / or a compound thereof and a phosphorus compound, and a catalyst containing an aluminum salt of a phosphorus compound.
[0014] The polyester film substrate in the present invention is particularly preferably a biaxially oriented film from the standpoint of practical properties such as strength and stiffness.
[0015] The layer structure of the polyester film substrate may be a single layer structure or a laminate structure, but a preferred embodiment is a laminate structure of A layer / B layer / A layer, in which the A layer contains inorganic particles and the B layer contains microvoids. By disposing a layer containing inorganic particles in the A layer, which is the surface layer, it is possible to improve the slipperiness, i.e., the handling property and the concealing property of the film, and by containing microvoids only in the B layer, which is the inner layer, a preferable white appearance is obtained, and it is possible to ensure the strength of the film surface while expressing the cushioning property of the film. Here, the method of forming the laminate structure is not particularly limited, but it is preferable to perform it by co-extrusion from the viewpoint of stability during production and processing costs.
[0016] The polyester film substrate in the present invention may have a single layer structure or a multilayer structure, but it is preferable that some or all of the layers are opaque. The optical density indicating the opacity of the white laminated polyester film is preferably 0.3 or more, more preferably 0.3 to 4.0, and particularly preferably 0.5 to 3.0. When the optical density is 0.3 or more, the printing effect becomes clear when printing is performed on the coating layer surface of the white laminated polyester film, which is preferable. When the optical density is 4.0 or less, a better printing effect can be expected, which is preferable.
[0017] The method for obtaining an optical density within the above range is not particularly limited, but can be achieved by incorporating inorganic particles or a thermoplastic resin incompatible with the polyester resin in the polyester resin. The content of these is not particularly limited, but in the case of inorganic particles, it is preferably 5 to 35 mass% relative to the produced polyester, and particularly preferably 8 to 25 mass%. On the other hand, in the case of incorporating an incompatible thermoplastic resin, it is preferably 5 to 35 mass% relative to the polyester, and particularly preferably 8 to 28 mass%. In addition, in the case of using inorganic particles and a thermoplastic resin incompatible with the polyester resin in combination, it is preferable that the total amount is 40 mass% or less relative to the polyester film substrate in terms of film strength, stiffness, and film formation stability.
[0018] The inorganic particles used are not particularly limited, but inorganic particles having an average particle size of 0.1 to 4.0 μm are preferred, and inorganic particles having an average particle size of 0.3 to 1.5 μm are particularly preferred. Specifically, white pigments such as titanium oxide, barium sulfate, calcium carbonate, and zinc sulfide are preferred, and these may be mixed. Furthermore, inorganic particles generally contained in films, such as silica, alumina, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconia, tungsten oxide, lithium fluoride, calcium fluoride, and calcium sulfate, may be used in combination.
[0019] In addition, the thermoplastic resin incompatible with the polyester resin is not particularly limited, but for example, when mixed with polyethylene terephthalate resin, polyolefin resins such as polystyrene resin, polyethylene resin, polypropylene resin, polymethylpentene resin, acrylic resin, phenoxy resin, polyphenylene oxide resin, polycarbonate resin, etc. can be mentioned. In addition, these thermoplastic resins may be mixed or modified. Of course, they can be used in combination with the above-mentioned inorganic particles. Needless to say, various whitening agents may be added as necessary.
[0020] The average particle size of the particles was measured by observing the particles on the cross section of the film with a scanning electron microscope, observing 50 particles, and taking the average value as the average particle size.
[0021] As long as the object of the present invention is satisfied, the shape of the particles is not particularly limited, and spherical particles and irregular non-spherical particles can be used. The particle diameter of irregular particles can be calculated as the circle equivalent diameter. The circle equivalent diameter is the value obtained by dividing the observed particle area by π, calculating the square root, and multiplying it by two.
[0022] Furthermore, the white laminated polyester film of the present invention has an apparent density of 0.3 to 1.3 g / cm 3 It is preferable that the polyester film is a microvoid-containing polyester film having the formula:
[0023] Also preferred is a white laminated polyester film having a cavity lamination density of 0.20 / μm or more, preferably 0.25 / μm or more, more preferably 0.30 / μm or more, from the viewpoint of achieving both cushioning properties and surface peel strength. As a result, the obtained white laminated polyester film has excellent print clarity and processing characteristics during printing. Here, the cavity lamination density (cavities / μm) is defined by the formula: number of cavities in the film thickness direction (cavities) / film thickness (μm). The upper limit of the cavity lamination density is preferably 0.80 / μm, more preferably 0.55 / μm, from the viewpoint of cavity expression efficiency. Methods for adjusting the density within the above range include, but are not limited to, adjusting the amount, type, viscosity, etc. of the incompatible thermoplastic resin to be added, changing the screw shape of the extruder, and installing a static mixer in the molten resin flow path.
[0024] These void-containing white laminated polyester films are particularly useful because the microvoids contained in the film cause light scattering at the interface with the polyester matrix, resulting in a further improvement in opacity and the reduction in the amount of inorganic particles added. Furthermore, the inclusion of microvoids in the film allows the substrate film itself to be made lighter, making it easier to handle, and also resulting in significant economic benefits such as reduced raw material and transportation costs.
[0025] As a method for obtaining such a white laminated polyester film, a publicly known method that has already been disclosed can be used, such as a method in which a thermoplastic resin that is incompatible with the polyester resin as described above is kneaded into a thermoplastic polyester resin matrix, and a sheet in which the incompatible resin is dispersed in the form of fine particles in the polyester resin is stretched at least in one axial direction to generate cavities around the incompatible resin fine particles.
[0026] The thickness of the resulting white laminated polyester film is preferably 5 to 300 μm. In particular, the thickness of a white laminated polyester film having a void lamination density of 0.20 / μm or more is preferably 20 to 300 μm, and more preferably 40 to 250 μm.
[0027] The whiteness required for use in printing materials can be expressed in color values. In particular, the color L value is a measure of brightness, with a higher value indicating whiter color. Furthermore, a higher color b value indicates a stronger yellow tint, and a lower value indicates a stronger blue tint. In other words, a high L value and a low b value indicate high whiteness, which means that the color appears whiter to the naked eye. This improves clarity when printed.
[0028] (Coating layer) In order to improve adhesion to UV ink and blocking resistance when water is applied, the white laminated polyester film of the present invention preferably has a coating layer formed by curing a composition containing a urethane resin having a polycarbonate structure and a branched structure, a crosslinking agent, and a polyester resin on at least one side. The coating layer in the coating layer is considered to be formed by curing a urethane resin or polyester resin having a polycarbonate structure and a branched structure crosslinked by a crosslinking agent, but since it is difficult to express the crosslinked chemical structure itself, it is expressed as being formed by curing a composition containing a urethane resin having a polycarbonate structure and a branched structure, a crosslinking agent, and a polyester resin. The coating layer may be provided on both sides of the polyester film substrate, or may be provided only on one side of the polyester film substrate, and a different type of resin coating layer may be provided on the other side.
[0029] The composition of each coating layer will be described in detail below. (Urethane resin having a polycarbonate structure and a branched structure) The urethane resin having a polycarbonate structure in the present invention preferably has at least a urethane bond portion derived from a polycarbonate polyol component and a polyisocyanate component, and a branched structure, and further contains a chain extender as necessary. The branched structure referred to here is preferably introduced by forming a branched molecular chain structure after synthesis and polymerization due to the presence of three or more terminal functional groups in any of the raw material components constituting the molecular chain.
[0030] In the urethane resin having a polycarbonate structure and a branched structure in the present invention, the lower limit of the number of terminal functional groups in the molecular chain is preferably 3, more preferably 4, due to the branched structure. If it is 3 or more, blocking resistance when water is attached can be improved, which is preferable. In the urethane resin having a polycarbonate structure in the present invention, the upper limit of the number of terminal functional groups in the molecular chain is preferably 6, due to the branched structure. If it is 6 or less, the resin can be stably dispersed in an aqueous solution, which is preferable.
[0031] The lower limit of the mass ratio of the polycarbonate polyol component to the polyisocyanate component (mass of the polycarbonate polyol component / mass of the polyisocyanate component) when synthesizing and polymerizing the urethane resin having a polycarbonate structure and a branched structure in the present invention is preferably 0.5, more preferably 0.6, even more preferably 0.7, particularly preferably 0.8, and most preferably 1.0. If it is 0.5 or more, it is preferable because the adhesion to UV ink can be improved. The upper limit of the mass ratio of the polycarbonate polyol component to the polyisocyanate component when synthesizing and polymerizing the urethane resin having a polycarbonate structure in the present invention is preferably 3.0, more preferably 2.2, even more preferably 2.0, particularly preferably 1.7, and most preferably 1.5. If it is 3.0 or less, it is preferable because the blocking resistance when water is attached can be improved.
[0032] The polycarbonate polyol component used for synthesizing and polymerizing the urethane resin having a polycarbonate structure and a branched structure in the present invention preferably contains an aliphatic polycarbonate polyol having excellent heat resistance and hydrolysis resistance. Examples of the aliphatic polycarbonate polyol include an aliphatic polycarbonate diol and an aliphatic polycarbonate triol, and the aliphatic polycarbonate diol is preferably used. Examples of the aliphatic polycarbonate diol used for synthesizing and polymerizing the urethane resin having a polycarbonate structure in the present invention include aliphatic polycarbonate diols obtained by reacting one or more diols such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, 1,8-nonanediol, neopentyl glycol, diethylene glycol, and dipropylene glycol with carbonates such as dimethyl carbonate, ethylene carbonate, and phosgene.
[0033] The number average molecular weight of the polycarbonate polyol in the present invention is preferably 1000 to 3000, more preferably 1200 to 2900, and most preferably 1500 to 2800. When it is 1000 or more, ink adhesion can be improved, which is preferable. When it is 3000 or less, blocking resistance when water is attached can be improved, which is preferable.
[0034] Examples of polyisocyanates used in the synthesis and polymerization of the urethane resin having a polycarbonate structure and a branched structure in the present invention include aromatic aliphatic diisocyanates such as xylylene diisocyanate, alicyclic diisocyanates such as isophorone diisocyanate, 4,4-dicyclohexylmethane diisocyanate, and 1,3-bis(isocyanatomethyl)cyclohexane, aliphatic diisocyanates such as hexamethylene diisocyanate and 2,2,4-trimethylhexamethylene diisocyanate, and polyisocyanates in which one or more of these compounds are added to trimethylolpropane or the like in advance. When the aromatic aliphatic diisocyanates, alicyclic diisocyanates, or aliphatic diisocyanates are used, there is no problem of yellowing, which is preferable. In addition, the coating film does not become too hard, and the stress caused by the heat shrinkage of the polyester film substrate can be alleviated, and the adhesion becomes good, which is preferable.
[0035] Examples of chain extenders include glycols such as ethylene glycol, diethylene glycol, 1,4-butanediol, neopentyl glycol, and 1,6-hexanediol; polyhydric alcohols such as glycerin, trimethylolpropane, and pentaerythritol; diamines such as ethylenediamine, hexamethylenediamine, and piperazine; amino alcohols such as monoethanolamine and diethanolamine; thiodiglycols such as thiodiethylene glycol; and water.
[0036] In order to form a branched structure in the urethane resin, for example, a method can be preferably adopted in which the polycarbonate polyol component, polyisocyanate, and chain extender are reacted at an appropriate temperature for an appropriate time, and then a compound having a tri- or higher functional hydroxyl group or isocyanate group is added and the reaction is allowed to proceed further.
[0037] Specific examples of compounds having three or more functional hydroxyl groups include caprolactone triol, glycerol, trimethylolpropane, butane triol, hexane triol, 1,2,3-hexane triol, 1,2,3-pentane triol, 1,3,4-hexane triol, 1,3,4-pentane triol, 1,3,5-hexane triol, 1,3,5-pentane triol, polyether triol, etc. Examples of the polyether triol include compounds obtained by addition polymerization of one or more monomers such as ethylene oxide, propylene oxide, butylene oxide, amylene oxide, glycidyl ether, methyl glycidyl ether, t-butyl glycidyl ether, and phenyl glycidyl ether, using one or more compounds having three active hydrogens, such as alcohols such as glycerin and trimethylolpropane, and diethylenetriamine, as initiators.
[0038] A specific example of a compound having a trifunctional or higher isocyanate group may be a polyisocyanate compound having at least three isocyanate (NCO) groups in one molecule. In the present invention, the trifunctional or higher isocyanate compound may be a biuret, a nurate, an adduct, or the like, which is a modified isocyanate monomer having two isocyanate groups, such as an aromatic diisocyanate, an aliphatic diisocyanate, an araliphatic diisocyanate, or an alicyclic diisocyanate. Examples of aromatic diisocyanates include 1,3-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,4-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-toluidine diisocyanate, dianisidine diisocyanate, and 4,4'-diphenyl ether diisocyanate. Examples of the aliphatic diisocyanate include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate. Examples of the aralkyl diisocyanate include xylylene diisocyanate, ω,ω'-diisocyanate-1,4-diethylbenzene, 1,4-tetramethylxylylene diisocyanate, and 1,3-tetramethylxylylene diisocyanate. Examples of alicyclic diisocyanates include 3-isocyanatemethyl-3,5,5-trimethylcyclohexyl isocyanate (also known as IPDI, isophorone diisocyanate), 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), and 1,4-bis(isocyanatemethyl)cyclohexane. The biuret form is a self-condensation product having a biuret bond formed by the self-condensation of an isocyanate monomer, and an example of such a product is a biuret form of hexamethylene diisocyanate. The nurate form is a trimer of an isocyanate monomer, and examples thereof include a trimer of hexamethylene diisocyanate, a trimer of isophorone diisocyanate, and a trimer of tolylene diisocyanate. The adduct refers to a tri- or higher functional isocyanate compound obtained by reacting the above-mentioned isocyanate monomer with a tri- or higher functional low-molecular-weight active hydrogen-containing compound. Examples of the adduct include a compound obtained by reacting trimethylolpropane with hexamethylene diisocyanate, a compound obtained by reacting trimethylolpropane with tolylene diisocyanate, a compound obtained by reacting trimethylolpropane with xylylene diisocyanate, and a compound obtained by reacting trimethylolpropane with isophorone diisocyanate.
[0039] Examples of chain extenders having three or more functional groups include trimethylolpropane and alcohols having three or more hydroxyl groups such as pentaerythritol, which are described above as chain extenders.
[0040] The coating layer in the present invention is preferably provided by an in-line coating method described below using a water-based coating liquid. Therefore, it is desirable that the urethane resin of the present invention is water-soluble or water-dispersible. The above-mentioned "water-soluble or water-dispersible" means that it is dispersible in water or an aqueous solution containing less than 50 mass% of a water-soluble organic solvent.
[0041] To impart water dispersibility to urethane resins, sulfonic acid (salt) groups or carboxylic acid (salt) groups can be introduced (copolymerized) into the urethane molecular structure. To maintain moisture resistance, it is preferable to introduce a weakly acidic carboxylic acid (salt) group. It is also possible to introduce a nonionic group such as a polyoxyalkylene group.
[0042] In order to introduce a carboxylic acid (salt) group into a urethane resin, for example, a polyol compound having a carboxylic acid group, such as dimethylolpropanoic acid or dimethylolbutanoic acid, is introduced as a copolymerization component as a polyol component, and neutralized with a salt-forming agent. Specific examples of salt-forming agents include ammonia, trialkylamines such as trimethylamine, triethylamine, triisopropylamine, tri-n-propylamine, and tri-n-butylamine, N-alkylmorpholines such as N-methylmorpholine and N-ethylmorpholine, and N-dialkylalkanolamines such as N-dimethylethanolamine and N-diethylethanolamine. These can be used alone or in combination of two or more kinds.
[0043] When a polyol compound having a carboxylic acid (salt) group is used as a copolymerization component to impart water dispersibility, the molar ratio of the polyol compound having a carboxylic acid (salt) group in the urethane resin is preferably 3 to 60 mol%, and more preferably 5 to 40 mol%, when the total polyisocyanate components of the urethane resin are taken as 100 mol%. When the molar ratio is 3 mol% or more, water dispersibility is obtained, which is preferable. Also, when the molar ratio is 60 mol% or less, water resistance is maintained and moist heat resistance is obtained, which is preferable.
[0044] The urethane resin in the present invention may have a blocked isocyanate structure at the end to improve hardness.
[0045] (Crosslinking agent) In the present invention, the crosslinking agent contained in the coating layer-forming composition is preferably a blocked isocyanate, more preferably a trifunctional or higher blocked isocyanate, and particularly preferably a tetrafunctional or higher blocked isocyanate, which can improve blocking resistance when water is attached.
[0046] The lower limit of the NCO equivalent of the blocked isocyanate is preferably 100, more preferably 120, even more preferably 130, particularly preferably 140, and most preferably 150. When the NCO equivalent is 100 or more, there is no risk of the coating cracking, which is preferable. The upper limit of the NCO equivalent is preferably 500, more preferably 400, even more preferably 380, particularly preferably 350, and most preferably 300. When the NCO equivalent is 500 or less, blocking resistance when water is attached can be improved, which is preferable.
[0047] The lower limit of the boiling point of the blocking agent of the blocked isocyanate is preferably 150°C, more preferably 160°C, even more preferably 180°C, particularly preferably 200°C, and most preferably 210°C. The higher the boiling point of the blocking agent, the more the volatilization of the blocking agent is suppressed even by the drying process after coating of the coating liquid or by heat addition in the film forming process in the case of the in-line coating method, the occurrence of minute unevenness on the coated surface is suppressed, and the transparency of the film is improved. The upper limit of the boiling point of the blocking agent is not particularly limited, but it is thought that the upper limit is about 300°C from the viewpoint of productivity. Since the boiling point is related to the molecular weight, in order to increase the boiling point of the blocking agent, it is preferable to use a blocking agent with a large molecular weight, and the molecular weight of the blocking agent is preferably 50 or more, more preferably 60 or more, and even more preferably 80 or more.
[0048] The upper limit of the dissociation temperature of the blocking agent is preferably 200°C, more preferably 180°C, even more preferably 160°C, particularly preferably 150°C, and most preferably 120°C. The blocking agent dissociates from the functional group by heat addition in the drying process after application of the coating liquid or in the case of the in-line coating method in the film formation process, and a regenerated isocyanate group is generated. Therefore, the crosslinking reaction with urethane resin etc. progresses, and the adhesiveness is improved. When the dissociation temperature of the blocked isocyanate is the above temperature or lower, the dissociation of the blocking agent progresses sufficiently, and the adhesiveness, especially the wet heat resistance, is good.
[0049] In the present invention, examples of blocking agents having a dissociation temperature of 120° C. or less and a boiling point of 150° C. or more used in the blocked isocyanate include bisulfite compounds such as sodium bisulfite, pyrazole compounds such as 3,5-dimethylpyrazole, 3-methylpyrazole, 4-bromo-3,5-dimethylpyrazole, 4-nitro-3,5-dimethylpyrazole, active methylene compounds such as malonic acid diesters (dimethyl malonate, diethyl malonate, di-n-butyl malonate, di-2-ethylhexyl malonate), methyl ethyl ketone, etc., and triazole compounds such as 1,2,4-triazole. Among these, pyrazole compounds are preferred from the viewpoints of resistance to moist heat and yellowing.
[0050] In the present invention, the trifunctional or higher polyisocyanate, which is a precursor of the blocked isocyanate, can be suitably obtained by introducing an isocyanate monomer, for example, a biuret, a nurate, an adduct, etc., which are obtained by modifying an isocyanate monomer such as an aromatic diisocyanate, an aliphatic diisocyanate, an araliphatic diisocyanate, or an alicyclic diisocyanate having two isocyanate groups. The biuret form is a self-condensation product having a biuret bond formed by the self-condensation of an isocyanate monomer, and an example of such a product is a biuret form of hexamethylene diisocyanate. The nurate form is a trimer of an isocyanate monomer, and examples thereof include a trimer of hexamethylene diisocyanate, a trimer of isophorone diisocyanate, and a trimer of tolylene diisocyanate. The adduct refers to a tri- or higher functional isocyanate compound obtained by reacting an isocyanate monomer with a tri- or higher functional low-molecular-weight active hydrogen-containing compound, and examples thereof include a compound obtained by reacting trimethylolpropane with hexamethylene diisocyanate, a compound obtained by reacting trimethylolpropane with tolylene diisocyanate, a compound obtained by reacting trimethylolpropane with xylylene diisocyanate, and a compound obtained by reacting trimethylolpropane with isophorone diisocyanate.
[0051] The isocyanate monomers include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, 1,5-naphthylene diisocyanate, 1,4-naphthylene diisocyanate, phenylene diisocyanate, tetramethylxylylene diisocyanate, 4,4'-diphenylether diisocyanate, 2-nitrodiphenyl-4,4'-diisocyanate, 2,2'-diphenylpropane-4,4'-diisocyanate, 3,3' Examples of the diisocyanates include aromatic diisocyanates such as 4,4'-dimethyldiphenylmethane diisocyanate, 4,4'-diphenylpropane diisocyanate, and 3,3'-dimethoxydiphenyl-4,4'-diisocyanate, aromatic aliphatic diisocyanates such as xylylene diisocyanate, alicyclic diisocyanates such as isophorone diisocyanate, 4,4-dicyclohexylmethane diisocyanate, and 1,3-bis(isocyanatemethyl)cyclohexane, and aliphatic diisocyanates such as hexamethylene diisocyanate and 2,2,4-trimethylhexamethylene diisocyanate. From the viewpoints of transparency, adhesion, and resistance to moisture and heat, aliphatic and alicyclic isocyanates and their modified products are preferred.
[0052] The blocked isocyanate of the present invention can introduce a hydrophilic group into the precursor polyisocyanate in order to impart water solubility or water dispersibility. Examples of hydrophilic groups include (1) quaternary ammonium salts of dialkylamino alcohols and quaternary ammonium salts of dialkylaminoalkylamines, (2) sulfonates, carboxylates, phosphates, and (3) polyethylene glycols and polypropylene glycols one-end-blocked with an alkyl group. When a hydrophilic moiety is introduced, the isocyanate becomes (1) cationic, (2) anionic, or (3) nonionic. Among them, since many other water-soluble resins are anionic, anionic or nonionic is preferred because they are easily compatible. In addition, anionic is highly compatible with other resins, and nonionic is preferred because it does not have an ionic hydrophilic group, in order to improve resistance to moist heat.
[0053] The anionic hydrophilic group is preferably one having a hydroxyl group for introduction into polyisocyanate and a carboxylic acid group for imparting hydrophilicity. Examples include glycolic acid, lactic acid, tartaric acid, citric acid, oxybutyric acid, oxyvaleric acid, hydroxypivalic acid, dimethylolacetic acid, dimethylolpropanoic acid, dimethylolbutanoic acid, and polycaprolactone having a carboxylic acid group. To neutralize the carboxylic acid group, an organic amine compound is preferred. Examples of the amine include linear or branched primary, secondary or tertiary amines having 1 to 20 carbon atoms, such as ammonia, methylamine, ethylamine, propylamine, isopropylamine, butylamine, 2-ethylhexylamine, cyclohexylamine, dimethylamine, diethylamine, dipropylamine, diisopropylamine, dibutylamine, trimethylamine, triethylamine, triisopropylamine, tributylamine, and ethylenediamine; cyclic amines, such as morpholine, N-alkylmorpholine, and pyridine; and hydroxyl group-containing amines, such as monoisopropanolamine, methylethanolamine, methylisopropanolamine, dimethylethanolamine, diisopropanolamine, diethanolamine, triethanolamine, diethylethanolamine, and triethanolamine.
[0054] As the nonionic hydrophilic group, the repeating units of ethylene oxide and / or propylene oxide of polyethylene glycol or polypropylene glycol capped at one end with an alkyl group are preferably 3 to 50, more preferably 5 to 30. If the repeating units are small, the compatibility with the resin is poor and the haze increases, and if they are large, the adhesiveness under high temperature and high humidity may decrease. In order to improve the water dispersibility, the blocked isocyanate of the present invention may be added with a nonionic, anionic, cationic or amphoteric surfactant. For example, surfactants such as polyethylene glycol, polyhydric alcohol fatty acid ester, etc., anionic fatty acid salt, alkyl sulfate ester, alkylbenzene sulfonate, sulfosuccinate, alkyl phosphate, etc., cationic alkylamine salt, alkylbetaine, etc., carboxylate amine salt, sulfonate amine salt, sulfate ester salt, etc. may be mentioned.
[0055] In addition to water, a water-soluble organic solvent may be contained. For example, the organic solvent used in the reaction may be removed and another organic solvent may be added.
[0056] (polyester resin) The polyester resin used to form the coating layer in the present invention may be a straight-chain one, but is more preferably a polyester resin composed of a dicarboxylic acid and a diol having a branched structure. The dicarboxylic acid referred to here includes aliphatic dicarboxylic acids such as adipic acid and sebacic acid, and aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and 2,6-naphthalenedicarboxylic acid, as well as terephthalic acid, isophthalic acid, phthalic acid, and 2,6-naphthalenedicarboxylic acid. The branched glycol is a diol having a branched alkyl group, and examples thereof include 2,2-dimethyl-1,3-propanediol, 2-methyl-2-ethyl-1,3-propanediol, 2-methyl-2-butyl-1,3-propanediol, 2-methyl-2-propyl-1,3-propanediol, 2-methyl-2-isopropyl-1,3-propanediol, 2-methyl-2-n-hexyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, 2-ethyl-2-n-butyl-1,3-propanediol, 2-ethyl-2-n-hexyl-1,3-propanediol, 2,2-di-n-butyl-1,3-propanediol, 2-n-butyl-2-propyl-1,3-propanediol, and 2,2-di-n-hexyl-1,3-propanediol.
[0057] It can be said that the polyester resin contains the branched glycol component, which is a more preferred embodiment of the above, in the total glycol components at a ratio of preferably 10 mol % or more, more preferably 20 mol % or more. If it is 10 mol % or less, the crystallinity becomes high and the adhesiveness of the coating layer may decrease. The upper limit of the glycol component in the total glycol components is preferably 80 mol % or less, more preferably 70 mass %. If it is 80 mol % or more, the concentration of oligomers, which are by-products, increases, which may affect the transparency of the coating layer. As the glycol component other than the above compounds, ethylene glycol is the most preferred. If it is a small amount, diethylene glycol, propylene glycol, butanediol, hexanediol, 1,4-cyclohexanedimethanol, etc. may be used.
[0058] The dicarboxylic acid as a component of the polyester resin is most preferably terephthalic acid or isophthalic acid. In addition to the dicarboxylic acid, in order to impart water dispersibility to the copolymerized polyester resin, it is preferable to copolymerize 5-sulfoisophthalic acid or the like in the range of 1 to 10 mol%, for example, sulfoterephthalic acid, 5-sulfoisophthalic acid, 5-sodium sulfoisophthalic acid, etc. A polyester resin containing a dicarboxylic acid having a naphthalene skeleton may be used, but in order to suppress a decrease in adhesion to UV ink, the quantitative ratio is preferably 5 mol% or less in the total carboxylic acid components, and it may not be used.
[0059] When the total solid content of the polyester resin, the urethane resin having a polycarbonate structure, and the crosslinking agent in the coating liquid is 100% by mass, the lower limit of the content of the crosslinking agent is preferably 5% by mass, more preferably 7% by mass, and even more preferably 10% by mass. If it is 5% by mass or more, blocking resistance when water is attached can be improved, which is preferable. The upper limit of the content of the crosslinking agent is preferably 50% by mass, more preferably 40% by mass, even more preferably 35% by mass, and most preferably 30% by mass. If it is 50% by mass or less, adhesion to UV ink is high, which is preferable.
[0060] When the total solid content of the polyester resin, the urethane resin having a polycarbonate structure, and the crosslinking agent in the coating liquid is 100% by mass, the lower limit of the content of the urethane resin having a polycarbonate structure is preferably 5% by mass. If it is 5% by mass or more, the adhesion to UV ink can be improved, which is preferable. The upper limit of the content of the urethane resin having a polycarbonate structure is preferably 50% by mass, more preferably 40% by mass, even more preferably 30% by mass, and most preferably 20% by mass. If the content of the urethane resin is 50% by mass or less, blocking resistance when water is attached can be improved, which is preferable.
[0061] When the total solid content of the polyester resin, urethane resin and crosslinking agent in the coating liquid is 100% by mass, the lower limit of the polyester resin content is preferably 10% by mass, more preferably 20% by mass, even more preferably 30% by mass, particularly preferably 35% by mass, and most preferably 40% by mass. If the polyester resin content is 10% by mass or more, the adhesion between the coating layer and the polyester film substrate becomes good, which is preferable. The upper limit of the polyester resin content is preferably 70% by mass, more preferably 67% by mass, even more preferably 65% by mass, particularly preferably 62% by mass, and most preferably 60% by mass. If the polyester resin content is 70% by mass or less, the moist heat resistance after UV ink processing becomes good, which is preferable.
[0062] (Additives) In the coating layer of the present invention, known additives such as surfactants, antioxidants, heat stabilizers, weather stabilizers, ultraviolet absorbers, organic lubricants, pigments, dyes, organic or inorganic particles, antistatic agents, nucleating agents, etc. may be added within the range that does not impair the effects of the present invention.
[0063] In the present invention, it is particularly preferable that the composition forming the coating layer further contains an antistatic agent, since this can prevent static electricity troubles during various steps for labeling the obtained film, such as coating with an adhesive, printing, cutting, punching, etc. As the antistatic agent, any of the following may be used as long as it does not impair the effects of the present invention: those generally used as coating-type antistatic agents (e.g., quaternary ammonium salt-based antistatic agents), particulate carbon black, metal powders such as nickel and copper, metal oxides such as tin oxide and zinc oxide, fibrous brass, stainless steel, metal-coated fibers such as aluminum, flake graphite, conductive fillers such as aluminum flakes, and copper flakes, and conductive polymers such as sulfonated polyaniline and polypyrrole.
[0064] In order to reduce the gloss of the coating layer surface, inert particles may be contained in the coating layer.
[0065] Examples of the inactive particles include inorganic particles such as titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silica, alumina, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconia, tungsten oxide, lithium fluoride, and calcium fluoride, and organic polymer particles such as polystyrene-based, polyacrylic-based, melamine-based, benzoguanamine-based, and silicone resin-based particles. These may be used alone or in combination of two or more.
[0066] The average particle size of the inert particles is preferably 0.1 to 2.4 μm, more preferably 0.3 to 2.0 μm. If the average particle size of the inert particles is 0.04 μm or less, the glossiness of the film surface may increase. Conversely, if the average particle size of the inert particles exceeds 2.4 μm, the particles tend to fall off from the coating layer, causing powdering.
[0067] The method for measuring the average particle size is as described above. The shape of the particles is not particularly limited as long as it satisfies the object of the present invention, and spherical particles and irregular non-spherical particles can be used. The particle size of irregular particles can be calculated as the circle equivalent diameter.
[0068] When it is desired to increase the gloss of the coating layer surface, it is also preferable not to contain particles in the coating layer.
[0069] (Production of white laminated polyester film) The method for producing the white laminated polyester film of the present invention is arbitrary and is not particularly limited, but for example, a general method can be used in which a mixture consisting of the above-mentioned composition is melted and extruded into a sheet to form an unstretched film, and then this unstretched film is stretched.
[0070] In the white laminated polyester film of the present invention, a thermoplastic resin incompatible with the polyester resin is dispersed in the polyester resin during the process of melting and extruding the film raw material. In the examples of the present invention, the polyester resin and the thermoplastic resin incompatible with the polyester resin are supplied in the form of pellets, but the present invention is not limited to this.
[0071] The raw material to be fed into the extruder for melt molding into a film is prepared by mixing these resins into pellets according to the desired composition. However, when a polyester resin and a polyolefin resin are used as the raw material for the void-containing polyester film of the substrate of the present invention, the specific gravity of the resins is significantly different between the two, so it is preferable to add a measure to prevent the pellets once mixed from segregating during the process of being fed into the extruder. A suitable method for preventing segregation is to combine a part or all of the raw resins in advance, knead and pelletize them to form master batch pellets. This method was used in the examples of the present invention, but it is not particularly limited as long as it does not interfere with the effects of the present invention.
[0072] In addition, when extruding a mixture of these incompatible resins, even after mixing and finely dispersing them in a molten state, they tend to re-aggregate due to the effect of reducing the interfacial energy of the resins. This phenomenon causes the void generating agent to become coarsely dispersed during extrusion molding of an unstretched film, preventing the desired physical properties from being expressed.
[0073] In order to prevent this, when forming the film of the present invention, it is preferable to finely disperse the void generating agent in advance using a twin-screw extruder with a higher mixing effect. If this is difficult, it is also preferable to supply the raw material resin from the extruder to the feed block or die through a static mixer as an auxiliary means. As the static mixer used here, a static mixer, an orifice, etc. can be used. However, when these methods are adopted, heat-degraded resin may be retained in the melt line, so care must be taken.
[0074] In addition, since the incompatible resin once dispersed in the polyester resin in the form of fine particles tends to re-aggregate over time under low shear molten conditions, the fundamental solution is to reduce the residence time in the melt line from the extruder to the die. In the present invention, the residence time in the melt line is preferably 30 minutes or less, and more preferably 15 minutes or less.
[0075] The conditions for stretching and orienting the unstretched film obtained as described above are closely related to the physical properties of the film. In the following, the stretching and orientation conditions will be explained using the most common sequential biaxial stretching method, particularly the method of stretching an unstretched film in the longitudinal direction and then in the transverse direction, as an example.
[0076] In the longitudinal stretching step, the film is stretched 2.5 to 5.0 times in the machine direction with rolls heated to 80 to 120°C to obtain a uniaxially stretched film. The heating means may be a method using a heated roll or a method using a non-contact heating method, or both may be used. The uniaxially stretched film is then introduced into a tenter and stretched 2.5 to 5.0 times in the width direction at a temperature of (Tm-10°C) or less. Here, Tm means the melting point of the polyester.
[0077] The biaxially stretched film is subjected to a heat treatment, if necessary. The heat treatment is preferably carried out in a tenter, and is preferably carried out within the range of (Tm-60°C) to Tm.
[0078] The coating layer can be provided after or during the film production process. In particular, from the viewpoint of productivity, it is preferable to form a coating layer by applying a coating liquid to at least one side of an unstretched or uniaxially stretched PET film at any stage of the film production process.
[0079] The coating solution can be applied to the PET film by any known method. For example, reverse roll coating, gravure coating, kiss coating, die coater, roll brush, spray coating, air knife coating, wire bar coating, pipe doctor, impregnation coating, curtain coating, etc. These methods can be used alone or in combination.
[0080] In the present invention, the thickness of the coating layer can be appropriately set in the range of 0.001 to 2.00 μm, but in order to achieve both processability and adhesiveness, the range is preferably 0.01 to 1.00 μm, more preferably 0.02 to 0.80 μm, and even more preferably 0.05 to 0.50 μm. If the thickness of the coating layer is 0.001 μm or more, the adhesiveness is good, which is preferable. If the thickness of the coating layer is 2.00 μm or less, blocking is less likely to occur, which is preferable.
[0081] Conventionally, many polyester films having coating layers containing polyester resins, polyurethane resins, acrylic resins, etc., either alone or in a mixture of two or more kinds, or a mixture of the above resins and a specific crosslinking agent (melamine, isocyanate, etc.), have satisfied blocking resistance when left in an environment containing normal water vapor. However, in winter, when transported between outdoors and indoors, condensation may occur and liquid water may adhere to the film surface or coating layer surface, and at that time, polyester films having coating layers containing polyester resins, polyurethane resins, acrylic resins, and crosslinking agents have a problem of blocking. However, the white laminated polyester film of the present invention not only has blocking resistance when left in an environment containing normal water vapor, but also has no risk of blocking when a highly adhesive polyester film transported between indoors and outdoors in winter condenses due to changes in environmental temperature and liquid water adheres to the film surface or coating layer surface. EXAMPLES
[0082] The present invention will now be described in detail with reference to examples and comparative examples, but the present invention is not limited to the following examples. First, the evaluation methods used in the present invention will be described below.
[0083] (1) Evaluation of blocking resistance when exposed to water The adhesive polyester film produced in the examples described below is cut to 10 cm in the width direction and 1.5 cm in the length direction. A film 1.5 cm in the width direction and 1.5 cm in the length direction is overlapped on the end of the coating layer surface of the cut film. 0.03 g of water droplets are dropped onto the coating layer surface at the opposite end. Then, the coating layer surfaces of the films cut to 10 cm in the width direction and 1.5 cm in the length direction are overlapped with each other, and rolled evenly so that air does not enter from the side where the water droplets were dropped to the side where the films are overlapped. Then, the sample is placed in an oven (50°C) for 24 hours. Then, the film is peeled off, and the peeling state is judged according to the following criteria. ◯: The coating layer was not transferred and could be easily peeled off. Δ: The coating layer is maintained, but the surface layer of the coating layer is partially transferred to the opposing surface. ×: The two films were stuck together and could not be peeled off, or even if they could be peeled off, the film base was cleaved.
[0084] (2) Adhesion to UV ink A UV ink [T&K TOKA Corporation, product name "BEST CURE UV161 Indigo S"] was used to print on the coating layer of the laminated polyester film using a printing machine [Akira Manufacturing Co., Ltd., product name "RI Tester"], and then the film with the ink layer was exposed to 40 mJ / cm using a high-pressure mercury lamp. 2 The ink was irradiated with ultraviolet light to cure the ultraviolet-curable ink. Next, a piece of cellophane adhesive tape (CT405AP-24) manufactured by Nichiban was cut out to a width of 24 mm and a length of 50 mm, and the tape was completely attached to the surface of the ink layer using a handy rubber roller so that no air was mixed in. The cellophane adhesive tape was then peeled off vertically, and the remaining area of the printed layer was observed in a 24 mm x 50 mm area, and judged according to the following criteria. ○: The remaining area of the printed layer is 99% or more of the total. △: The remaining area of the printed layer is 90% or more but less than 99% of the total. ×: Less than 90% of the printed layer remains
[0085] (3) Method for measuring number average molecular weight of polycarbonate polyol When a urethane resin having a polycarbonate structure is measured by proton nuclear magnetic resonance spectroscopy (1H-NMR), a peak derived from a methylene group adjacent to an OCOO bond is observed at around 4.1 ppm. In addition, a peak derived from a methylene group adjacent to a urethane bond generated by the reaction of a polyisocyanate with a polycarbonate polyol is observed about 0.2 ppm higher than the peak. The number average molecular weight of the polycarbonate polyol was calculated from the integral value of these two peaks and the molecular weight of the monomer that constitutes the polycarbonate polyol.
[0086] (4) Apparent density The film was cut into four square pieces, each 5.00 cm on each side, to prepare the samples. Then, measure the thickness at 10 points with a micrometer to four significant digits, and calculate the average thickness. This average value was divided by 4 and rounded off to the fourth decimal place to obtain the average frame rate per sheet. The film thickness (t: μm) was calculated to the third decimal place. The mass (w: g) of the four samples was also calculated. The apparent density was calculated using the following formula: , apparent densities were rounded to three significant figures. Apparent density (g / cm 3 )=w×10 4 / (5.00×5.00×t×4)
[0087] (5) Optical density Opacity of polyester film: Using a Macbeth densitometer TR-927, the transmittance of light through a G filter was measured, and the optical density was calculated from the obtained light transmittance, which was used as an index of opacity. Optical density is expressed as the logarithm (Log10) of the reciprocal of the light transmittance (range: 0-100%). A higher optical density value indicates higher opacity.
[0088] (6) L value, b value The reflected color L value and color b value were measured using a color difference meter (ZE6000, manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS-8722.
[0089] (Polymerization of urethane resin A-1 having a polycarbonate structure) Into a four-neck flask equipped with a stirrer, a Dimroth condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 27.5 parts by mass of hydrogenated m-xylylene diisocyanate, 6.5 parts by mass of dimethylolpropanoic acid, 60 parts by mass of polyhexamethylene carbonate diol having a number average molecular weight of 1800, 6 parts by mass of neopentyl glycol, and 84.00 parts by mass of acetone as a solvent were added, and the mixture was stirred for 3 hours at 75°C under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. Next, 5 parts by mass of trimethylolpropane were added, and the mixture was stirred for 1 hour at 75°C under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. After lowering the temperature of this reaction liquid to 40°C, 5.17 parts by mass of triethylamine were added to obtain a polyurethane prepolymer solution. Next, 450g of water was added to a reaction vessel equipped with a homodisper capable of high-speed stirring, and the temperature was adjusted to 25°C, and the mixture was stirred for 2000min. -1 The polyurethane prepolymer solution was added while stirring and mixing at 40° C., and dispersed in water. Then, the acetone and a part of the water were removed under reduced pressure to prepare a water-dispersible urethane resin solution (A-1) with a solid content of 34% by mass.
[0090] (Polymerization of urethane resin A-2 having a polycarbonate structure) Into a four-neck flask equipped with a stirrer, a Dimroth condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 25 parts by mass of 4,4-dicyclohexylmethane diisocyanate, 5 parts by mass of dimethylolpropanoic acid, 52 parts by mass of polyhexamethylene carbonate diol having a number average molecular weight of 2600, 6 parts by mass of neopentyl glycol, and 84.00 parts by mass of acetone as a solvent were added, and the mixture was stirred for 3 hours at 75°C under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. Next, 18 parts by mass of a polyisocyanate compound having an isocyanurate structure made from hexamethylene diisocyanate (manufactured by Asahi Kasei Chemicals, Duranate TPA, trifunctional) was added, and the mixture was stirred for 1 hour at 75°C under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. Thereafter, the reaction liquid temperature was lowered to 50°C, and 8 parts by mass of methyl ethyl ketoxime was added dropwise. After the reaction solution was cooled to 40°C, 5.17 parts by mass of triethylamine was added to obtain a polyurethane prepolymer solution. Next, 450 g of water was added to a reaction vessel equipped with a homodisperser capable of high speed stirring, and the temperature was adjusted to 25°C and stirred for 2000 min. -1 The polyurethane prepolymer solution was added while stirring and mixing at 40° C. to disperse the mixture in water. Then, the acetone and a portion of the water were removed under reduced pressure to prepare a water-dispersible urethane resin solution (A-2) with a solid content of 35% by mass.
[0091] (Polymerization of urethane resin A-3 having a polycarbonate structure) Into a four-neck flask equipped with a stirrer, a Dimroth condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 22 parts by mass of 4,4-dicyclohexylmethane diisocyanate, 20 parts by mass of polyethylene glycol monomethyl ether having a number average molecular weight of 700, 53 parts by mass of polyhexamethylene carbonate diol having a number average molecular weight of 2100, 5 parts by mass of neopentyl glycol, and 84.00 parts by mass of acetone as a solvent were added, and the mixture was stirred for 3 hours at 75°C under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. Next, 16 parts by mass of a polyisocyanate compound having an isocyanurate structure made from hexamethylene diisocyanate as a raw material (Asahi Kasei Chemicals, Duranate TPA, trifunctional) was added, and the mixture was stirred for 1 hour at 75°C under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. Thereafter, the reaction liquid temperature was lowered to 50°C, and 7 parts by mass of methyl ethyl ketoxime was added dropwise. After the reaction solution was cooled to 40° C., a polyurethane prepolymer solution was obtained. Next, 450 g of water was added to a reaction vessel equipped with a homodisperser capable of high speed stirring, and the temperature was adjusted to 25° C. and stirred for 2000 min. -1 The polyurethane prepolymer solution was added while stirring and mixing at 40° C. to disperse the mixture in water. Then, the acetone and a portion of the water were removed under reduced pressure to prepare a water-dispersible urethane resin solution (A-3) with a solid content of 35% by mass.
[0092] (Polymerization of urethane resin A-4 having a polycarbonate structure) 22 parts by mass of 4,4-dicyclohexylmethane diisocyanate, 3 parts by mass of dimethylol butanoic acid, 73 parts by mass of polyhexamethylene carbonate diol having a number average molecular weight of 2000, 2 parts by mass of neopentyl glycol, and 84.00 parts by mass of acetone as a solvent were added to a four-neck flask equipped with a stirrer, a Dimroth condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, and the mixture was stirred for 3 hours at 75°C under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. Next, 4 parts by mass of trimethylolpropane were added, and the mixture was stirred for 1 hour at 75°C under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. Next, the reaction liquid was cooled to 40°C, and then 8.77 parts by mass of triethylamine was added to obtain a polyurethane prepolymer solution. Next, 450 g of water was added to a reaction vessel equipped with a homodisper capable of high-speed stirring, and the temperature was adjusted to 25°C, and the mixture was stirred for 2000 min. -1 The polyurethane prepolymer solution was added while stirring and mixing at 40° C. to disperse the mixture in water. Then, the acetone and part of the water were removed under reduced pressure to prepare a water-dispersible urethane resin solution (A-4) with a solid content of 34% by mass.
[0093] (Polymerization of urethane resin A-5 having a polycarbonate structure) Into a four-neck flask equipped with a stirrer, a Dimroth condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 47 parts by mass of 4,4-dicyclohexylmethane diisocyanate, 21 parts by mass of polyethylene glycol monomethyl ether having a number average molecular weight of 700, 20 parts by mass of polyhexamethylene carbonate diol having a number average molecular weight of 1200, 12 parts by mass of neopentyl glycol, and 84.00 parts by mass of acetone as a solvent were added, and the mixture was stirred for 3 hours at 75°C under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. Next, 4 parts by mass of trimethylolpropane were added, and the mixture was stirred for 1 hour at 75°C under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. Next, after lowering the temperature of this reaction liquid to 40°C, 8.77 parts by mass of triethylamine were added to obtain a polyurethane prepolymer solution. Next, 450 g of water was added to a reaction vessel equipped with a homodisper capable of high-speed stirring, and the temperature was adjusted to 25°C, and the mixture was stirred for 2000 min.-1 The polyurethane prepolymer solution was added while stirring and mixing at 40° C. to disperse the mixture in water. Then, the acetone and part of the water were removed under reduced pressure to prepare a water-dispersible urethane resin solution (A-5) with a solid content of 34% by mass.
[0094] (Polymerization of urethane resin A-6 having a polycarbonate structure) 23.5 parts by mass of 4.4-dicyclohexylmethane diisocyanate, 4.5 parts by mass of dimethylol butanoic acid, 70 parts by mass of polyhexamethylene carbonate diol having a number average molecular weight of 2000, 2 parts by mass of neopentyl glycol, and 84.00 parts by mass of acetone as a solvent were added to a four-neck flask equipped with a stirrer, a Dimroth condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, and the mixture was stirred at 75°C for 3 hours under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. Next, the reaction liquid was cooled to 40°C, and then 8.77 parts by mass of triethylamine was added to obtain a polyurethane prepolymer solution. Next, 450 g of water was added to a reaction vessel equipped with a homodisper capable of high-speed stirring, and the temperature was adjusted to 25°C, and the mixture was stirred for 2000 min. -1 The polyurethane prepolymer solution was added while stirring and mixing at 40° C. to disperse the mixture in water. Then, the acetone and a portion of the water were removed under reduced pressure to prepare a water-dispersible urethane resin solution (A-6) with a solid content of 34% by mass.
[0095] (Polymerization of urethane resin A-7 having a polycarbonate structure) Into a four-neck flask equipped with a stirrer, a Dimroth condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 27.5 parts by mass of hydrogenated m-xylylene diisocyanate, 6.5 parts by mass of dimethylolpropanoic acid, 60 parts by mass of polyhexamethylene carbonate diol having a number average molecular weight of 1800, 6 parts by mass of neopentyl glycol, and 84.00 parts by mass of acetone as a solvent were added, and the mixture was stirred for 3 hours at 75°C under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. After lowering the temperature of this reaction liquid to 40°C, 5.17 parts by mass of triethylamine were added to obtain a polyurethane prepolymer solution. Next, 450g of water was added to a reaction vessel equipped with a homodisper capable of high-speed stirring, and the temperature was adjusted to 25°C, and the mixture was stirred for 2000min. -1 The polyurethane prepolymer solution was added while stirring and mixing at 40° C. to disperse the mixture in water. Then, the acetone and part of the water were removed under reduced pressure to prepare a water-dispersible urethane resin solution (A-7) with a solid content of 34% by mass.
[0096] (Polymerization of urethane resin A-8 having a polycarbonate structure) Into a four-neck flask equipped with a stirrer, a Dimroth condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 400 parts by mass of polycarbonate polyol consisting of 1,6-hexanediol and diethyl carbonate and having a number average molecular weight of 2000, 10.4 parts by mass of neopentyl glycol, 58.4 parts by mass of isophorone diisocyanate, 74.3 parts by mass of dimethylol butanoic acid, and 320 parts by mass of acetone as a solvent were added, and the mixture was stirred at 75°C for 3 hours under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. After lowering the temperature of this reaction liquid to 40°C, isophorone diamine was added to obtain a polyurethane prepolymer solution. Next, 1200 g of water was added to a reaction vessel equipped with a homodisper capable of high-speed stirring, and the temperature was adjusted to 25°C, and the mixture was stirred for 2000 min. -1 The polyurethane prepolymer solution was added while stirring and mixing at 40° C. to disperse the mixture in water. Then, the acetone and a portion of the water were removed under reduced pressure to prepare a water-dispersible urethane resin solution (A-8) with a solid content of 34% by mass.
[0097] (Polymerization of urethane resin A-9 having a polycarbonate structure) Into a four-neck flask equipped with a stirrer, a Dimroth condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 50 parts by mass of 4,4-dicyclohexylmethane diisocyanate, 21 parts by mass of polyethylene glycol monomethyl ether having a number average molecular weight of 700, 35 parts by mass of polyhexamethylene carbonate diol having a number average molecular weight of 1200, 13 parts by mass of neopentyl glycol, and 84.00 parts by mass of acetone as a solvent were added, and the mixture was stirred for 3 hours at 75°C under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. Next, 1.2 parts by mass of trimethylolpropane was added, and the mixture was stirred for 1 hour at 75°C under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. Next, after lowering the temperature of this reaction liquid to 40°C, 8.77 parts by mass of triethylamine was added to obtain a polyurethane prepolymer solution. Next, 450 g of water was added to a reaction vessel equipped with a homodisper capable of high-speed stirring, and the temperature was adjusted to 25°C, and the mixture was stirred for 2000 min. -1 The polyurethane prepolymer solution was added while stirring and mixing at 40° C. to disperse the mixture in water. Then, the acetone and part of the water were removed under reduced pressure to prepare a water-dispersible urethane resin solution (A-9) with a solid content of 34% by mass.
[0098] (Polymerization of urethane resin A-10 not containing polycarbonate polyol component) 75 parts by mass of polyester polyol having a molecular weight of 5000 and composed of terephthalic acid, isophthalic acid, ethylene glycol, and neopentyl glycol, 30 parts by mass of hydrogenated m-xylylene diisocyanate, 7 parts by mass of ethylene glycol, 6 parts by mass of dimethylolpropionic acid, and 84.00 parts by mass of acetone as a solvent were added, and the mixture was stirred at 75°C for 3 hours under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. After lowering the temperature of this reaction liquid to 40°C, 5.17 parts by mass of triethylamine were added to obtain a polyurethane prepolymer solution. Next, 450g of water was added to a reaction vessel equipped with a homodisper capable of high-speed stirring, and the temperature was adjusted to 25°C, and the mixture was stirred for 2000min. -1The polyurethane prepolymer solution was added while stirring and mixing at 40° C. to disperse the mixture in water. Then, the acetone and a portion of the water were removed under reduced pressure to prepare a water-dispersible urethane resin solution (A-10) with a solid content of 34% by mass.
[0099] (Polymerization of urethane resin A-11 not containing polycarbonate polyol component) Into a four-neck flask equipped with a stirrer, a Dimroth condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 54 parts of 4,4-dicyclohexylmethane diisocyanate, 38 parts by mass of polyester polyol having a number average molecular weight of 1500 and composed of ethylene glycol and adipic acid, 0.8 parts by mass of trimethylolpropane, and 84.00 parts by mass of acetone as a solvent were added, and the mixture was stirred for 3 hours at 75°C under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. Next, 4 parts by mass of sodium hydrogen sulfate were added, and the mixture was stirred for 1 hour at 75°C under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. Next, after lowering the temperature of this reaction liquid to 40°C, 8.77 parts by mass of triethylamine were added to obtain a polyurethane prepolymer solution. Next, 450 g of water was added to a reaction vessel equipped with a homodisper capable of high-speed stirring, and the temperature was adjusted to 25°C, and the mixture was stirred for 2000 min. -1 The polyurethane prepolymer solution was added while stirring and mixing at 40° C. to disperse the mixture in water. Then, the acetone and part of the water were removed under reduced pressure to prepare a water-dispersible urethane resin solution (A-11) with a solid content of 34% by mass.
[0100] (Polymerization of blocked isocyanate crosslinking agent B-1) In a flask equipped with a stirrer, a thermometer, and a reflux condenser, 66.04 parts by mass of a polyisocyanate compound having an isocyanurate structure made from hexamethylene diisocyanate (Asahi Kasei Chemicals, Duranate TPA), 17.50 parts by mass of N-methylpyrrolidone, and 95 parts by mass of 3,5-dimethylpyrazole (dissociation temperature: 120 ° C, boiling point: 218 ° C) were dropped, and the mixture was kept at 70 ° C for 1 hour under a nitrogen atmosphere. Then, 30 parts by mass of dimethylolpropanoic acid were dropped. After measuring the infrared spectrum of the reaction solution and confirming that the absorption of the isocyanate group had disappeared, 5.59 parts by mass of N,N-dimethylethanolamine and 132.5 parts by mass of water were added to obtain a blocked polyisocyanate aqueous dispersion (B-1) with a solid content of 40% by mass. The functional group number of the blocked isocyanate crosslinking agent is 4, and the NCO equivalent is 280.
[0101] (Polymerization of blocked isocyanate crosslinking agent B-2) A flask equipped with a stirrer, a thermometer, and a reflux condenser was charged with 100 parts by mass of a polyisocyanate compound having an isocyanurate structure made from hexamethylene diisocyanate (Asahi Kasei Chemicals, Duranate TPA), 55 parts by mass of propylene glycol monomethyl ether acetate, and 30 parts by mass of polyethylene glycol monomethyl ether (average molecular weight 750), and the mixture was kept at 70°C for 4 hours under a nitrogen atmosphere. Thereafter, the reaction liquid temperature was lowered to 50°C, and 47 parts by mass of methyl ethyl ketoxime was added dropwise. The infrared spectrum of the reaction liquid was measured to confirm that the absorption of the isocyanate group had disappeared, and 210 parts by mass of water was added to obtain an oxime-blocked isocyanate crosslinking agent (B-2) with a solid content of 40% by mass. The number of functional groups of the blocked isocyanate crosslinking agent was 3, and the NCO equivalent was 170.
[0102] (Polymerization of carbodiimide B-3) A flask equipped with a stirrer, a thermometer, and a reflux condenser was charged with 168 parts by mass of hexamethylene diisocyanate and 220 parts by mass of polyethylene glycol monomethyl ether (M400, average molecular weight 400), and stirred at 120 ° C for 1 hour. Further, 26 parts by mass of 4,4'-dicyclohexylmethane diisocyanate and 3.8 parts by mass of 3-methyl-1-phenyl-2-phospholene-1-oxide (2% by mass relative to the total isocyanate) were added as a carbodiimide catalyst, and the mixture was stirred at 185 ° C for another 5 hours under a nitrogen stream. The infrared spectrum of the reaction solution was measured, and it was confirmed that the absorption at wavelengths of 220 to 2300 cm-1 had disappeared. The mixture was allowed to cool to 60 ° C, and 567 parts by mass of ion-exchanged water was added to obtain a carbodiimide aqueous resin solution (B-3) with a solid content of 40% by mass.
[0103] (Polymerization of blocked isocyanate crosslinking agent B-4) 33.6 parts by mass of hexamethylene diisocyanate was added to 200 parts by mass of a polyester (molecular weight 2000) of ethylene oxide 2 moles adduct of bisphenol A and maleic acid, and the mixture was reacted at 100° C. for 2 hours. The temperature of the system was then lowered to 50° C., 73 parts by mass of a 30% aqueous sodium bisulfite solution was added, and the mixture was stirred at 45° C. for 60 minutes, after which it was diluted with 718 parts by mass of water to obtain a blocked polyisocyanate aqueous dispersion (B-1) with a solid content of 20% by mass. The blocked isocyanate crosslinking agent had a functional group number of 2 and an NCO equivalent of 1300.
[0104] (Polymerization of polyester resin C-1) In a stainless steel autoclave equipped with a stirrer, a thermometer, and a partial reflux condenser, 194.2 parts by mass of dimethyl terephthalate, 184.5 parts by mass of dimethyl isophthalate, 14.8 parts by mass of dimethyl-5-sodium sulfoisophthalate, 233.5 parts by mass of diethylene glycol, 136.6 parts by mass of ethylene glycol, and 0.2 parts by mass of tetra-n-butyl titanate were charged, and an ester exchange reaction was carried out at a temperature of 160°C to 220°C for 4 hours. The temperature was then raised to 255°C, and the reaction system was gradually depressurized, and the reaction was carried out for 1 hour and 30 minutes under a reduced pressure of 30 Pa to obtain a copolymer polyester resin (C-1). The obtained copolymer polyester resin (C-1) was pale yellow and transparent. The reduced viscosity of the copolymer polyester resin (C-1) was measured and found to be 0.70 dl / g. The glass transition temperature measured by DSC was 40°C.
[0105] (Preparation of polyester water dispersion Cw-1) In a reactor equipped with a stirrer, a thermometer, and a reflux device, 25 parts by mass of polyester resin (C-1) and 10 parts by mass of ethylene glycol n-butyl ether were placed, and the resin was dissolved by heating and stirring at 110°C. After the resin was completely dissolved, 65 parts by mass of water was gradually added to the polyester solution while stirring. After the addition, the liquid was cooled to room temperature while stirring to produce a milky white polyester water dispersion (Cw-1) with a solid content of 25% by mass.
[0106] (Polymerization of polyester resin C-2) In a stainless steel autoclave equipped with a stirrer, a thermometer, and a partial reflux condenser, 342.0 parts by mass of dimethyl 2,6-naphthalenedicarboxylate, 35.0 parts by mass of dimethyl terephthalate, 35.5 parts by mass of dimethyl-5-sodium sulfoisophthalate, 198.6 parts by mass of ethylene glycol, 118.2 parts by mass of 1,6-hexanediol, and 0.4 parts by mass of tetra-n-butyl titanate were charged, and an ester exchange reaction was carried out over 4 hours from 160°C to 220°C. Furthermore, 60.7 parts by mass of sebacic acid was added to carry out an esterification reaction. The temperature was then raised to 255°C, and the reaction system was gradually reduced in pressure, and the reaction was carried out for 1 hour and 30 minutes under a reduced pressure of 30 Pa to obtain a copolymer polyester resin (C-2). The obtained copolymer polyester resin was pale yellow and transparent.
[0107] (Preparation of polyester water dispersion Cw-2) In a reactor equipped with a stirrer, a thermometer, and a reflux device, 25 parts by mass of copolymerized polyester resin (C-2) and 15 parts by mass of ethylene glycol-n-butyl ether were placed, and the mixture was heated to 110°C and stirred to dissolve the resin. After the resin was completely dissolved, 55 parts by mass of water was gradually added to the polyester solution while stirring. After the addition, the liquid was cooled to room temperature while stirring to produce a milky white polyester water dispersion (Cw-2) with a solid content of 25% by mass.
[0108] (Polymerization of polyester resin C-3) In a stainless steel autoclave equipped with a stirrer, a thermometer, and a partial reflux condenser, 194.2 parts by mass of dimethyl terephthalate, 184.5 parts by mass of dimethyl isophthalate, 14.8 parts by mass of dimethyl-5-sodium sulfoisophthalate, 185 parts by mass of neopentyl glycol, 188 parts by mass of ethylene glycol, and 0.2 parts by mass of tetra-n-butyl titanate were charged, and an ester exchange reaction was carried out at a temperature of 160°C to 220°C for 4 hours. The temperature was then raised to 255°C, and the reaction system was gradually depressurized, and the reaction was carried out for 1 hour and 30 minutes under a reduced pressure of 30 Pa to obtain a copolymer polyester resin (C-3). The obtained copolymer polyester resin (C-3) was pale yellow and transparent. The reduced viscosity of the copolymer polyester resin (C-3) was measured and found to be 0.40 dl / g. The glass transition temperature measured by DSC was 65°C.
[0109] (Preparation of polyester water dispersion Cw-3) In a reactor equipped with a stirrer, a thermometer, and a reflux device, 25 parts by mass of polyester resin (C-3) and 10 parts by mass of ethylene glycol n-butyl ether were placed, and the mixture was heated to 110°C and stirred to dissolve the resin. After the resin was completely dissolved, 65 parts by mass of water was gradually added to the polyester solution while stirring. After the addition, the liquid was cooled to room temperature while stirring to produce a milky white polyester water dispersion (Cw-3) with a solid content of 25% by mass.
[0110] Example 1 (1) Preparation of coating solution The following coating agent was mixed into a mixed solvent of water and isopropanol to prepare a coating solution with a solids mass ratio of urethane resin solution (A-1) / crosslinking agent (B-1) / polyester water dispersion (Cw-1) of 25 / 26 / 49. Urethane resin solution (A-1) 6.30 parts by weight Crosslinking agent (B-1) 5.50 parts by mass Polyester water dispersion (Cw-1) 17.00 parts by mass Particles 23.00 parts by mass (Silica particles with an average particle size of 0.45 μm, solid content concentration of 40.00% by mass) Surfactant: 0.15 parts by weight (Silicone-based, solids concentration 10% by weight)
[0111] (2) Manufacturing of white laminated polyester film (Preparation of Master Pellet) A pellet mixture of 60% by mass of polymethylpentene resin (DX820, manufactured by Mitsui Chemicals) with a melt viscosity (ηO) of 1,300 poise, 20% by mass of polystyrene resin (G797N, manufactured by Nippon Polystyrene Co., Ltd.) with a melt viscosity (ηS) of 3,900 poise, and 20% by mass of polypropylene resin (J104WC, manufactured by Grand Polymer Co., Ltd.) with a melt viscosity of 2,000 poise was fed to a vented twin-screw extruder adjusted to 285°C and pre-mixed. This molten resin was continuously fed to a vented single-screw kneader, kneaded and extruded, and the resulting strand was cooled and cut to prepare a cavity generating agent master pellet (M1).
[0112] In addition, 50% by mass of polyethylene terephthalate resin with an intrinsic viscosity of 0.62 dl / g produced by a known method was mixed with 50% by mass of anatase type titanium dioxide particles (manufactured by Fuji Titanium Co., Ltd., TA-300) with an average particle size of 0.3 μm, and the mixture was fed to a vented twin-screw extruder and pre-mixed. This molten resin was continuously fed to a vented single-screw kneader, kneaded, and extruded. The obtained strand was cooled and cut to prepare titanium dioxide-containing master pellets (M2).
[0113] (Preparation of film raw materials) 81% by mass of the polyethylene terephthalate resin having an intrinsic viscosity of 0.62 dl / g that had been vacuum dried at 140°C for 8 hours, 9% by mass of the master pellets (M1) that had been vacuum dried at 90°C for 4 hours, and 10% by mass of the master pellets (M2) were pellet-mixed to prepare a film raw material (C1).
[0114] (Preparation of Unstretched Film) The film raw material (C1) was mixed with 70% by mass of the same polyethylene terephthalate resin used in the film raw material (C1) and 30% by mass of the master pellets (M2) in the B layer extruder adjusted to 285° C., and the resultant mixture was fed separately to the A layer extruder adjusted to 290° C. The molten resin discharged from the B layer extruder was guided to a feedbook via an orifice, and the resin discharged from the A layer extruder was guided to a feedbook via a static mixer, and a layer (B layer) made of the film raw material (C1) and a layer (A layer) made of the polyethylene terephthalate resin and the master pellets (M2) were laminated in the order of A layer / B layer / A layer.
[0115] The molten resin was co-extruded from a T-die onto a cooling roll adjusted to 25°C in the form of a sheet, and was solidified by electrostatic application to produce an unstretched film with a thickness of 510 μm. The discharge rate of each extruder was adjusted so that the thickness ratio of each layer was 1:8:1. The residence time of the molten resin in the melt line was approximately 12 minutes, and the shear rate received from the T-die was approximately 150 / sec.
[0116] (Preparation of biaxially stretched film) The unstretched film obtained was uniformly heated to 65°C using a heating roll, and stretched 3.4 times longitudinally between two pairs of nip rolls (low-speed roll: 2 m / min, high-speed roll: 6.8 m / min) with different peripheral speeds. At this time, an infrared heater (rated output: 20 W / cm) equipped with a gold reflective film in the middle of the nip roll was installed at a position 1 cm from the film surface facing both sides of the film as an auxiliary heating device for the film. The above-mentioned coating liquid was applied to one side of the uniaxially stretched film obtained in this way by the reverse kiss coat method so that the resin solid thickness before stretching was 0.9 μm. After coating, it was introduced into a tenter, heated to 150°C while drying, and stretched 3.7 times transversely, fixed in width and heat-treated at 220°C for 5 seconds, and further relaxed in the width direction by 4% at 200°C to obtain a white laminated polyester film with a thickness of 50 μm. The apparent density of this film was 1.10 g / cm 3 The optical density was 0.8. The evaluation results are shown in Table 1.
[0117] Example 2 A white laminated polyester film was obtained in the same manner as in Example 1, except that the urethane resin in the coating liquid was changed to (A-2) and the polyester water dispersion was changed to (Cw-3).
[0118] Example 3 (1) Preparation of coating solution A coating liquid was prepared in the same manner as in Example 1, except that the urethane resin was changed to (A-3).
[0119] (2) Manufacturing of white laminated polyester film (Preparation of Master Pellet) A mixture of 50% by mass of polyethylene terephthalate resin with an intrinsic viscosity of 0.62 and 50% by mass of anatase-type titanium dioxide with an average particle size of 0.3 μm (by electron microscopy) was fed into a vented twin-screw extruder and kneaded to produce titanium oxide-containing master pellets (M3).
[0120] (Preparation of Unstretched Film) 85% by mass of polyethylene terephthalate resin with an intrinsic viscosity of 0.62, 10% by mass of polypropylene resin with MFR=2.5, Mw=320000, Mw / Mn=4.0, and deflection temperature under load=92°C, and 5% by mass of the titanium oxide-containing master pellets (M3) were mixed and dried in a vacuum to obtain a raw material for the void-containing polyester B layer. Meanwhile, 30% by mass of the titanium oxide-containing master pellets (M3) and 70% by mass of polyethylene terephthalate resin with an intrinsic viscosity of 0.62 were pellet-mixed and dried in a vacuum to obtain a raw material for the inorganic particle-containing polyester A layer. These raw materials were fed into separate extruders, melted at 285°C, laminated so that the void-containing polyester B layer and the inorganic particle-containing polyester A layer were in the order of A / B / A, and joined by a feed block so that the thickness ratio was 10 / 80 / 10, and extruded from a T-die onto a cooling drum adjusted to 30°C to produce an unstretched film with a two-kind three-layer structure.
[0121] (Preparation of biaxially stretched film) The unstretched film obtained was uniformly heated to 70°C using a heating roll, and stretched 3.4 times longitudinally between two pairs of nip rolls with different peripheral speeds. At this time, an infrared heater (rated at 20 W / cm) equipped with a gold reflective film in the middle of the nip roll was installed facing both sides of the film (at a distance of 1 cm from the film surface) as an auxiliary heating device for the film. The above coating liquid was applied to one side of the uniaxially stretched film obtained in this manner by a reverse kiss coat method so that the resin solid thickness before stretching was 0.9 μm. After coating, the film was introduced into a tenter, heated to 140°C while drying, stretched laterally 4.0 times, fixed in width, heat-treated at 235°C, and further relaxed in the width direction by 3% at 210°C to obtain a white laminated polyester film with a thickness of 50 μm. The apparent density of this film was 1.09 g / cm 3 The optical density was 0.6, the L value was 94.4 and the b value was 1.6.
[0122] Example 4 A white laminated polyester film was obtained in the same manner as in Example 1, except that the crosslinking agent in the coating liquid was changed to (B-2).
[0123] Example 5 A white laminated polyester film was obtained in the same manner as in Example 1, except that the urethane resin in the coating liquid was changed to (A-2) and the crosslinking agent was changed to (B-2).
[0124] Example 6 A white laminated polyester film was obtained in the same manner as in Example 1, except that the urethane resin in the coating liquid was changed to (A-3) and the crosslinking agent was changed to (B-2).
[0125] Example 7 In the coating solution, the following coating agent was mixed into a mixed solvent of water and isopropanol, and the solid mass ratio of the urethane resin solution (A-2) / total of the crosslinking agents (B-1, B-2) / polyester water dispersion (Cw-1) was changed to 25 / 26 / 49. A white laminated polyester film was obtained in the same manner as in Example 1. Urethane resin solution (A-2) 6.30 parts by weight Crosslinking agent (B-1) 3.73 parts by mass Crosslinking agent (B-2) 1.77 parts by mass Polyester water dispersion (Cw-1) 17.00 parts by mass Particles 23.00 parts by mass (Silica particles with an average particle size of 0.45 μm, solid content concentration of 40.00% by mass) Surfactant: 0.15 parts by weight (Silicone-based, solids concentration 10% by weight)
[0126] Example 8 A white laminated polyester film was obtained in the same manner as in Example 7, except that the urethane resin in the coating liquid was changed to (A-3) and the polyester water dispersion was changed to (Cw-3).
[0127] Example 9 In the coating solution, the following coating agent was mixed into a mixed solvent of water and isopropanol, and the solid mass ratio of the urethane resin solution (A-3) / crosslinking agent (B-2) / polyester water dispersion (Cw-1) was changed to 27 / 14 / 59. A white laminated polyester film was obtained in the same manner as in Example 1. Urethane resin solution (A-3) 7.00 parts by mass Crosslinking agent (B-2) 3.00 parts by mass Polyester water dispersion (Cw-1) 21.00 parts by mass Particles 23.00 parts by mass (Silica particles with an average particle size of 0.45 μm, solid content concentration of 40.00% by mass) Surfactant: 0.15 parts by weight (Silicone-based, solids concentration 10% by weight) Antistatic agent 2.00 parts by weight (Quaternary ammonium salt-based antistatic agent, solids concentration 17.50% by mass)
[0128] Example 10 In the coating solution, the following coating agent was mixed into a mixed solvent of water and isopropanol, and the solid mass ratio of the urethane resin solution (A-3) / crosslinking agent (B-2) / polyester water dispersion (Cw-1) was changed to 28 / 11 / 61. A white laminated polyester film was obtained in the same manner as in Example 1. Urethane resin solution (A-3) 12.00 parts by mass Crosslinking agent (B-2) 4.00 parts by mass Polyester water dispersion (Cw-1) 35.00 parts by mass Particles 27.00 parts by mass (Benzoguanamine formaldehyde condensate particles with an average particle size of 2 μm, Solid content concentration 40.00% by mass) MB6 Surfactant: 0.15 parts by weight (Silicone-based, solids concentration 10% by weight) Antistatic agent 2.00 parts by weight (Quaternary ammonium salt-based antistatic agent, solids concentration 17.50% by mass)
[0129] Example 11 In the coating solution, the following coating agent was mixed into a mixed solvent of water and isopropanol, and the solid mass ratio of the urethane resin solution (A-1) / crosslinking agent (B-1) / polyester water dispersion (Cw-1) was changed to 22 / 10 / 68. A laminated polyester film was obtained in the same manner as in Example 1. Urethane resin solution (A-1) 5.80 parts by mass Crosslinking agent (B-1) 2.20 parts by mass Polyester water dispersion (Cw-1) 24.00 parts by mass Particles 23.00 parts by mass (Silica particles with an average particle size of 0.45 μm, solid content concentration of 40.00% by mass) Surfactant: 0.15 parts by weight (Silicone-based, solids concentration 10% by weight)
[0130] Example 12 A laminated polyester film was obtained in the same manner as in Example 11, except that the urethane resin in the coating liquid was changed to (A-2).
[0131] Example 13 A laminated polyester film was obtained in the same manner as in Example 11, except that the urethane resin in the coating liquid was changed to (A-3).
[0132] Example 14 A laminated polyester film was obtained in the same manner as in Example 11, except that the crosslinking agent in the coating liquid was changed to (B-3) and the polyester water dispersion was changed to (Cw-3).
[0133] Example 15 A laminated polyester film was obtained in the same manner as in Example 11, except that the urethane resin in the coating liquid was changed to (A-4).
[0134] (Example 16) A laminated polyester film was obtained in the same manner as in Example 11, except that the urethane resin in the coating liquid was changed to (A-5).
[0135] (Example 17) A laminated polyester film was obtained in the same manner as in Example 11, except that the urethane resin in the coating liquid was changed to (A-3) and the crosslinking agent was changed to (B-2).
[0136] (Example 18) A laminated polyester film was obtained in the same manner as in Example 11, except that the urethane resin in the coating liquid was changed to (A-3) and the particles were changed to calcium carbonate particles having an average particle size of 1 μm (solid content concentration 40.00 mass %).
[0137] (Example 19) A laminated polyester film was obtained in the same manner as in Example 11, except that the urethane resin in the coating liquid was changed to (A-9).
[0138] Comparative Example 1 A laminated polyester film was obtained in the same manner as in Example 1, except that the urethane resin in the coating liquid was changed to (A-6).
[0139] Comparative Example 2 A laminated polyester film was obtained in the same manner as in Example 1, except that the urethane resin in the coating liquid was changed to (A-7).
[0140] Comparative Example 3 A laminated polyester film was obtained in the same manner as in Example 11, except that the urethane resin in the coating liquid was changed to (A-6).
[0141] Comparative Example 4 A laminated polyester film was obtained in the same manner as in Example 11, except that the urethane resin in the coating liquid was changed to (A-7).
[0142] Comparative Example 5 A laminated polyester film was obtained in the same manner as in Example 1, except that the solid mass ratio of the coating liquid urethane resin solution (A-6) / crosslinking agent (B-1) / polyester water dispersion (Cw-2) was changed to 38 / 7 / 55.
[0143] Comparative Example 6 A laminated polyester film was obtained in the same manner as in Example 1, except that the solid mass ratio of the coating liquid urethane resin solution (A-8) / crosslinking agent (B-4) / polyester water dispersion (Cw-2) was changed to 22 / 12 / 66.
[0144] As shown in Table 1, each Example achieved satisfactory results in terms of blocking resistance when water was attached and adhesion to UV ink. On the other hand, in Comparative Examples 1 to 6, the coating layer formed on at least one surface of the polyester film substrate did not contain a urethane resin having a branched structure, and therefore the blocking resistance when water was attached was not satisfactory.
[0145] Comparative Example 7 In the coating solution, the following coating agent was mixed into a mixed solvent of water and isopropanol, and the solid content ratio of the urethane resin solution (A-1) / crosslinking agent (B-1) was changed to 70 / 30. A laminated polyester film was obtained in the same manner as in Example 1. Urethane resin solution (A-1) 15.00 parts by mass Crosslinking agent (B-1) 5.50 parts by mass Particles 23.00 parts by mass (Silica particles with an average particle size of 0.45 μm, solid content concentration of 40.00% by mass) Surfactant: 0.15 parts by weight (Silicone-based, solids concentration 10% by weight)
[0146] Comparative Example 8 In the coating solution, the following coating agent was mixed into a mixed solvent of water and isopropanol, and the solid content ratio of the urethane resin solution (A-1) / crosslinking agent (B-1) was changed to 20 / 80. A laminated polyester film was obtained in the same manner as in Example 1. Urethane resin solution (A-1) 4.70 parts by mass Crosslinking agent (B-1) 16.00 parts by mass Particles 23.00 parts by mass (Silica particles with an average particle size of 0.45 μm, solid content concentration of 40.00% by mass) Surfactant: 0.15 parts by weight (Silicone-based, solids concentration 10% by weight)
[0147] As shown in Table 1, in Comparative Examples 7 and 8, the coating layer formed on at least one side of the polyester film substrate did not contain polyester resin, so the adhesion between the coating layer and the substrate was reduced and the adhesion to UV ink was not satisfactory.
[0148] Comparative Example 9 A laminated polyester film was obtained in the same manner as in Example 1, except that the urethane resin was changed to (A-10).
[0149] Comparative Example 10 A laminated polyester film was obtained in the same manner as in Example 11, except that the urethane resin was changed to (A-11).
[0150] As shown in Table 1, in Comparative Examples 9 and 10, the coating layer formed on at least one side of the polyester film substrate did not contain a urethane resin having a polycarbonate structure, and therefore the adhesion to UV ink was not satisfactory.
[0151] Table 1 summarizes the evaluation results of each of the examples and comparative examples.
[0152] [Table 1] [Industrial Applicability]
[0153] According to the present invention, it is possible to provide a white laminated polyester film that can be suitably used in fields such as label applications.
Claims
1. A white laminated polyester film having a coating layer on at least one surface of a polyester resin layer, the coating layer being formed by curing a composition containing a urethane resin having a polycarbonate structure and a branched structure, a crosslinking agent, a polyester resin, and an antistatic agent.
2. 2. The white laminated polyester film according to claim 1, wherein the crosslinking agent is a compound having a tri- or higher functional blocked isocyanate group.
3. The laminated polyester film according to claim 1, wherein the urethane resin having a polycarbonate structure and a branched structure is obtained by synthesizing and polymerizing a polycarbonate polyol component and a polyisocyanate component, and a mass ratio of the polycarbonate polyol component to the polyisocyanate component (mass of the polycarbonate polyol component / mass of the polyisocyanate component) during the synthesis and polymerization is 0.5 to 3.
4. A label having the white laminated polyester film described in claim 1.
Citation Information
Patent Citations
Easily adhesive white polyester film
JP2011140542A
Laminated polyester film
JP2014196461A
Production of optical easy adhesive film
JP2000229355A